Islamic Media, Objectivity, and Islamic Communication Ethics in the Post-Truth Era - M. Yakub; Ahmad Sampurna (DAWUH : Islamic Communication Journal, 2026)
This research analyzes the confrontation between the principles of Islamic Communication Ethics (PEKI) which include Shiddiq (factual truthfulness), Tabayyun (verification), and Al-'Adl (narrative justice) and the reality of the Post-Truth Era within the development of Islamic media. The Post-Truth Era is defined by the dominance of emotions and ideological sentiments over objective facts, amplified by digital audience fragmentation and algorithms. The methodology employed is a comprehensive qualitative literature study, supported by a theoretical case study analysis on the failure of Tabayyun and Al-'Adl amidst sensitive religious issues. The findings indicate that the objectivity of Islamic media is under serious threat, where the demands for virality and group solidarity often override ethical obligations. The proposed solution is the revitalization of PEKI into a new epistemological foundation, termed Substantive Objectivity. This revitalization requires Islamic media to integrate Shiddiq with modern fact-checking procedures, uphold Al-'Adl as universal representational justice, and adopt the Wasatiyyah (moderation) approach to counter narrative polarization. The conclusion asserts that an implementational commitment to PEKI is crucial for Islamic media to reclaim factual authority, maintain Amanah (trustworthiness), and function as an agent of social cohesion amidst information chaos.